Factors associated with adequate antenatal care use among women of childbearing age in Burkina Faso: finding from the 2010 and 2021 demographic and health surveys - Badolo, Hermann; Bado, Aristide Romaric; Bazié, Herman; Bacyé, Yisso Fidèle; Konseiga, Romaine; Hien, Hervé (Frontiers in Public Health, 2025)
IntroductionAntenatal care (ANC) is a critical determinant of maternal and infant wellbeing and is a reliable method for reducing maternal and infant mortality. Antenatal care use is considered adequate when the first ANC takes place in the first trimester and the woman completes at least four ANC in accordance with WHO recommendations during her pregnancy. Despite the increasing of the proportion of women having completed at least four ANC in Burkina Faso, the data show that WHO recommendations are far from being respected. This study aimed to determine the evolution of individual, family and community factors associated with the adequate use of ANC in Burkina Faso between 2010 and 2021.MethodsThe data used in this study is procured from the Demographic and Health Surveys carried out in Burkina Faso in 2010 and 2021. Binary logistic regression analysis was used to analyze factors associated with the use of antenatal care. Adjusted odds ratios (AOR) were estimated to assess the strength of associations, and 95% confidence intervals were used for significance testing. A proportion test was used to examine differences in ANC utilization between 2010 and 2021 in Burkina Faso.ResultsIn our study sample, 22.92% (95% CI: 22.11–23.74) of the respondents in 2010 had adequate ANC use, compared to 46.34% (95% CI: 45.12–47.58) in 2021. The results demonstrate the influence of the woman’s individual characteristics, the household and the community characteristics on the adequate ANC use in Burkina Faso. Regarding the woman’s individual characteristics, age, educational level, marital status, occupation and modern contraceptive methods use were significantly associated with adequate ANC use in 2010 and 2021. The household wellbeing quintile, the degree of exposure to the media and the region of residence were significantly associated with adequate antenatal care use in 2010 and 2021.ConclusionThis study notes that Burkina Faso has made enormous progress in improving the coverage of antenatal care between 2010 and 2021, and indicates several factors including individual, family and community factors influencing adequate ANC use. For optimal efficacy, interventions promoting the adoption of antenatal care services must take these outcomes into account.